Biosafety considerations triggered by genome-editing technologies - Xinxin Li; Yuanjiao Gao; Ziyu Zhang; Wen Deng; Weihua Cao; Xin Wei; Zixuan Gao; Linmei Yao; Shuojie Wang; Yao Xie; Minghui Li (Biosafety and Health, 2025)
Since the discovery of the double helix structure of deoxyribonucleic acid (DNA), significant progress has been made in engineering technologies such as gene analysis and editing, greatly promoting the development of biomedical research and clinical applications. In recent years, the rapid development of genome-editing technologies, especially the clustered regularly interspaced short palindromic repeats-associated protein 9 (CRISPR-Cas9) system, have brought unprecedented opportunities for biomedical research and clinical applications. However, with the widespread application of genome-editing technologies, biosafety issues have gradually attracted the attention of the scientific community and the public. Potential risks such as off-target effects, genomic instability, and ethical and legal issues need to be taken seriously, and their safety and effectiveness in clinical applications still require further verification. This review summarizes the current status and potential risks of gene editing technologies in the medical field and discusses how to ensure its safe application through policies, regulations, and technical means. Through in-depth exploration of these issues, we hope to provide a comprehensive perspective for the scientific community, policy makers, and the public to promote the safe and responsible application of genome-editing technologies.